2015
DOI: 10.1016/j.jds.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Root canal morphology analysis of maxillary permanent first and second molars in a southeastern Turkish population using cone-beam computed tomography

Abstract: Background/purpose: The aim of this retrospective study was to determine the root and canal morphology of the maxillary first and second molars in a Turkish subpopulation using cone-beam computed tomography (CBCT). Materials and methods: CBCT images of 417 women and 410 men aged 14e70 years were examined. A total of 1158 maxillary permanent first molars and 1305 maxillary permanent second molars were analyzed. The number of root canals and canal configurations were investigated and classified according to Vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
20
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 20 publications
8
20
2
1
Order By: Relevance
“…The mesiobuccal root of the maxillary first molar with three independent roots was more prone to exhibit two root canals (71.05%). These data are in line with the results obtained in Turkey (Altunsoy et al 2015), India (Felsypremila et al 2015), the United States (Guo et al 2014) and in Asiatic countries such as Korea (Kim et al 2012) and China (Zhang et al 2011b, Tian et al 2016. Other studies from Brazil (Silva et al 2014), Italy (Plotino et al 2013) and India (Neelakantan et al 2010) reported prevalences of a single root canal (Vertucci Type I) in 52.87%, 59.7% and 51.8% of cases, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The mesiobuccal root of the maxillary first molar with three independent roots was more prone to exhibit two root canals (71.05%). These data are in line with the results obtained in Turkey (Altunsoy et al 2015), India (Felsypremila et al 2015), the United States (Guo et al 2014) and in Asiatic countries such as Korea (Kim et al 2012) and China (Zhang et al 2011b, Tian et al 2016. Other studies from Brazil (Silva et al 2014), Italy (Plotino et al 2013) and India (Neelakantan et al 2010) reported prevalences of a single root canal (Vertucci Type I) in 52.87%, 59.7% and 51.8% of cases, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…These data are in line with the results obtained in Turkey (Altunsoy et al . ), India (Felsypremila et al . ), the United States (Guo et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root canals that have not been completely treated or are missed are the main causes of failure of endodontic therapy [ 5 , 6 ]. The configuration of root canals in human teeth is quite complicated and varies among different populations and races [ 3 , 7 , 8 ]. However, the complexity of the internal anatomical structure is usually masked by the relatively simple external anatomy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Altunsoy et al(17) determinaron la raíz y la morfología del conducto de los primeros molares y segundos maxilares en una subpoblación de Turquía con el uso de tomografía de haz cónico computarizada (CBCT). Tanto en las primeras y segundas molares superiores, la presencia de tres raíces fue la ocurrencia más común.…”
unclassified